Requirements Negotiation: Making System Stakeholders’ Multiple-views One - Ahmad, S. (David Publishing, 2011)
The requirements engineering activities within a software project are known to be critical to the successful production of a correctly functioning system. This is particularly so when considering the varying views of multiple stakeholders. One promising approach for improving the outcome is to introduce formal negotiation. Clearly, making the set of requirements more closely represent all the stakeholders’ perspectives and perceptions, underpins a sound basis for project estimation, improved system quality and a reduction of the resources necessary. However, such benefits are mere speculation if it is not possible to provide empirical evidence. This paper presents a framework to provide empirical evidence on the effectiveness of formal negotiation to identify and to resolve conflicts between stakeholders. In particular, it is valuable in the allocation of priorities for a particular requirement and in the decision on its inclusion or exclusion. This is particularly useful in evolutionary and incremental paradigms such as the Agile methods. Also, it is necessary when time and resources are constrained - a condition in most software projects. Whereas this outcome is hardly surprising, it does validate the fundamental purpose of negotiation.